Long-run productivity trends: A global update with a global index - Jens J. Krüger (Review of Development Economics, 2020)
This paper documents the results from a macroeconomic total factor productivity analysis with a special focus on disentangling efficiency change and technological change under variable returns to scale. A sample of 93 countries is investigated by nonparametric methods. For the measurement three variants of the Malmquist index (basic, biennial, and global) are used. Specific country groups and selected individual countries are examined. The results show that productivity development is mainly driven by the interplay of technological change and efficiency change with a reversal from a backward shifting frontier function until the mid-1990s to an advancing frontier thereafter.
Keywords: 330; macroeconomic productivity; Malmquist index; nonparametric measurement